Optimasi Formula Granul Effervescent Ekstrak Rimpang Temu Putih (Curcuma zedoaria) dengan Variasi Pemanis Alami sebagai Antioksidan: Optimization and Antioxidant Evaluation of Effervescent Granules Containing White Turmeric (Curcuma zedoaria) Rhizome Extract with Natural Sweeteners - Diki Zaelani; Ratu Siti Robiatul Awaliyah; Rahmat Santoso; Emma Emawati; Reza Pratama (Bachelor of Pharmacy Study Program, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2025)
White turmeric (Curcuma zedoaria), a member of the Zingiberaceae family, contains bioactive compounds with antioxidant potential, but its utilization remains limited due to its bitter taste and less practical traditional preparations. This study aimed to optimize the formulation of effervescent granules containing white turmeric rhizome extract using different natural sweeteners and to evaluate their physical properties and antioxidant activity. The effervescent granules were prepared by the wet granulation method using stevia (F1, 17.5%), palm sugar (F2, 10%), and corn sugar (F3, 14.5%) as sweeteners. The granules were evaluated for physical characteristics (organoleptic properties, moisture content, flow rate, angle of repose, dissolution time, pH, foam height, and hedonic test) and antioxidant activity using the DPPH method both qualitatively and quantitatively. The results showed that all formulas met the standard physical requirements of effervescent granules. The best formulation was obtained from F3 (corn sugar) with the highest acceptance score in the hedonic test. The antioxidant activity of white turmeric extract exhibited an IC₅₀ value of 53.53 ppm, while the effervescent granules showed strong antioxidant activity with IC₅₀ values of 62.53 ppm (F1), 62.62 ppm (F2), and 62.79 ppm (F3). These findings indicate that variations in natural sweeteners influence the sensory characteristics without significantly reducing the antioxidant potency of the formulation. Keywords: Effervescent granules; Curcuma zedoaria; Natural sweeteners; Antioxidant, Formulation optimization.